Algal polysaccharides–Selenium nanoparticles regulate the uptake and distribution of selenium in rice plants - Yang, Chunmei; Wang, Chaoxin; Khan, Zaid; Duan, Songpo; Li, Zhiming; Shen, Hong (Frontiers in Plant Science, 2023)
Introduction Selenium (Se) is an essential trace element required for proper human and animal health. Methods In this paper, we investigated the uptake and distribution characteristics of a new Se fertilizer, which comprises algal polysaccharides–selenium nanoparticles (APS-SeNPs), in rice plants in both hydroponic and pot experiments. Results The results from the hydroponic experiments revealed that the rice root uptake of APS-SeNPs fitted the Michaelis–Menten equation, with a Vmax of 13.54 μg g−1 root dry weight (DW) per hour, which was 7.69 and 2.23 times those of selenite and selenate treatments, respectively. The root uptake of APS-SeNPs was inhibited by AgNO3 (64.81%–79.09%) and carbonyl cyanide 3-chlorophenylhydrazone (CCCP; 19.83%–29.03%), indicating that the uptake of APS-SeNPs by rice roots is mainly via aquaporins and is also affected by metabolic activity. Moreover, sulfur deficiency caused rice roots to absorb more APS-SeNPs, but treatment with APS-SeNPs increased the expression of the sulfate transporter OsSULTR1;2 in the roots, suggesting that OsSULTR1;2 is probably involved in the uptake of APS-SeNPs. The application of APS-SeNPs significantly increased the Se content in rice plants and the apparent Se uptake efficiency compared with selenate and selenite treatments. Most of the Se in the roots of rice plants was distributed in the cell wall, while it was primarily located in the cytosol in the shoots when treated with APS-SeNPs. The results from the pot experiments indicated that the application of Se enhanced the Se content of each rice tissue. It is worth noting that the Se content in brown rice under APS-SeNP treatment was higher than that under selenite or selenate treatment and was mainly concentrated in the embryo end, with the Se in organic form. Discussion Our findings provide important insights into the uptake mechanism and the distribution of APS-SeNPs in rice plants.